Loneliness is associated with maladaptive schema modes in patients with persistent depressive disorder. (October 2022) - Reinhard, Matthias A.; Popov, Naomi; Rek, Stephanie V.; Nenov-Matt, Tabea; Barton, Barbara B.; Jobst, Andrea; Musil, Richard; Padberg, Frank
Abstract: Objectives: Though loneliness represents a public health concern, this complex unpleasant feeling is commonly neglected in psychiatric care and may constitute a new treatment target in clinical groups particularly prone to feeling lonely and socially isolated, e.g., persistent depressive disorder (PDD). Schema modes encompass a set of distinct cognitive-affective patterns that may contribute to loneliness and social isolation. Aim of this study was to examine the interplay between subjective loneliness and objective social network size with schema modes in patients with PDD as well as healthy controls (HC). Method: Sixty-two PDD patients (DSM-5; 35 female, Mage = 40.5, SD = 12.4) and 71 HC (60 female, Mage = 28.1, SD = 10.1) were assessed cross-sectionally using the following self-report measures: UCLA Loneliness Scale, Social Network Index (SNI), and Schema-Mode-Inventory, revised version (SMI-r). Correlational and multiple linear regression analyses were performed. Results: PDD patients reported significantly higher scores of loneliness and maladaptive schema modes and a smaller social network than HC. Loneliness was significantly positively associated with the modes Vulnerable Child, Detached Protector, Bully and Attack, and Punitive Parent, and negatively with Contented Child and Healthy Adult in both groups. In contrast, social network size was only positively associated with the Contented Child mode. Conclusion: Loneliness is highly prevalent in PDD and in contrast to social network size associated with maladaptive schema modes. Therapeutically addressing these schema modes with specific techniques may represent a mechanism-based intervention for patients suffering from loneliness and should be investigated in clinical trials. Highlights: Dysfunctional schema modes are prevalent in patients with persistent depressive disorder (PDD). Loneliness is associated with dysfunctional schema modes both in patients with PDD and healthy controls. Addressing specific schema modes may be a promising approach to reduce loneliness.